Doing business in global arena: an examination of the relationship between cultural intelligence and cross-cultural adjustment - Sri Ramalu, Subramaniam; Che Rose, Raduan; Kumar, Naresh; Uli, Jegak (Asian Academy of Management and Penerbit Universiti Sains Malaysia, 2010)
The study examines the relationship between cultural intelligence (CQ) and cross-cultural adjustment (CCA) using a field study of 332 expatriates in Malaysia. The findings of this study reveal that CQ is a vital cross-cultural competency that facilitates expatriates CCA in international assignment. Specifically, the result of this study reveals that greater general adjustment is related to greater motivational and meta-cognitive CQ. The more successful interaction adjustment is associated with greater motivational, metacognitive and cognitive CQ. Greater work adjustment is related to greater motivational CQ. Motivational component of CQ is the only dimensions of CQ that is significantly related to all three dimensions of CCA. The findings of this study have significant contribution to the body of knowledge in the cross-cultural management field as well as practical implication to expatriating firms especially in the area of selection and hiring of international candidates.